Modeling Online Classroom Interaction to Support Student Language Learning - Sulistyani Sulistyani; Rika Riwayatiningsih (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2020)
For many years, teacher-student interaction has been indicated to considerably affect student learning. In recent years, research concentration has moved from attempting to evaluate the potent ways of classroom interaction for student learning and how it can be developed. Due to the intricacy of the classroom interaction procedure, the answer to this question is profoundly contingent upon some reasons, such as the learning condition. The aim of this project is to study the classroom interaction process in an online learning context in which English is learned as a foreign language.  This is review research employing content analysis technique we intend to examine the published research articles to find out the teachers’ strategies/tools and the contribution of the strategies to students’ language learning in online classroom interaction. This can build up an understanding of the most effective techniques to develop the students’ involvement with the learning process.  The result of the analysis is that most teachers use synchronous and asynchronous online classroom interaction and blended learning in which teacher-students, student-student, student-teacher, and student-learning sources are met through discussion. This strategy is mostly preferred by teachers to give students a chance to get involved in communication, collaboration, interaction, and participation. This strategy is believed to be able to engage students in developing language learning opportunities; therefore, this can be a good model for better classroom practices.